Rencana Aksi Nagari Tageh Nagari Lubuk Gadang Selatan Kecamatan Sangir Kabupaten Solok Selatan dalam Menghadapi Pandemi Covid-19 - Syamsurizaldi Syamsurizaldi; Fillia Agustin Coirala; Supriyanto Supriyanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
Nagari Tageh is an ongoing program to help the nagari in Nagari Lubuk Gadang Selatan, Sangir District, and South Solok Regency. This program is intended to assist the Nagari government in improving Nagari's governance, managing Nagari's potential and formulating a strategic plan in dealing with the Covid-19 pandemic in Nagari Lubuk Gadang Selatan. The Nagari potent in the agricultural sector, especially plantation crops and livestock, and tourism and services. As a Nagari located in a strategic area, but until now, it has not been status as an independent Nagari. Community service activities were carried out through mentoring and partnerships to assist Nagari in strengthening capacity and institutions to strengthen governance and development of Nagari in improving community welfare. In the first year (2020), there has been dissemination, focus group discussion and workshops with the Nagari government, community institutions at the Nagari level and other relevant stakeholders in Nagari Lubuk Gadang Selatan to explore problems formulating the Nagari Tageh action plan for 2021-2023. The Nagari Tageh action plan is implemented through a synergy and integration approach with the Government Work Plan (RKP) and the Nagari Revenue and Expenditure Budget (APB) 2021-2023.